2002
DOI: 10.2174/1381612023396654
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Sedative Effects of Benzodiazepine Use

Abstract: This paper reviews the effects of benzodiazepines (BZs) on the performance of tasks measuring human cognitive abilities. The paper reviews the most common cognitive side effects of BZs: increased sedation, decreased attention, and anterograde amnesia. In particular, this paper focuses on recent findings regarding time course-related effects on BZ-induced deficits in explicit and implicit human memory performance. Specifically, we reviewed recent research indicating that both explicit memory and priming are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
138
0
7

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(151 citation statements)
references
References 1 publication
6
138
0
7
Order By: Relevance
“…Given the nature of the anxiety ratings on the m-YPAS, which include not only arousal and displays of emotion, but also vocalizations and activity, this calming effect in the midazolam group at mask placement could be due to a combination of the sedative and the anxiolytic effects of the drug. 16 This finding is in agreement with previous studies which also found that midazolam has an anxiolytic effect if given to children as a pre-medicant. 9,10 The significant decrease in observer-rated anxiety levels for midazolam, compared to placebo, was not evident at post-drug baseline.…”
Section: Discussionsupporting
confidence: 93%
“…Given the nature of the anxiety ratings on the m-YPAS, which include not only arousal and displays of emotion, but also vocalizations and activity, this calming effect in the midazolam group at mask placement could be due to a combination of the sedative and the anxiolytic effects of the drug. 16 This finding is in agreement with previous studies which also found that midazolam has an anxiolytic effect if given to children as a pre-medicant. 9,10 The significant decrease in observer-rated anxiety levels for midazolam, compared to placebo, was not evident at post-drug baseline.…”
Section: Discussionsupporting
confidence: 93%
“…Instead they bypass the brain's processing systems and act directly on mechanisms that control emotion (Nesse and Berridge 1997). Too often pharmacological treatments, such as anxiolytic drugs, have limited long term efficacy (Youngstedt and Kripke 2007), are symptom based, and are associated with severe side effects including adverse reactions, dependency (Buffett-Jerrott and Stewart 2002), addiction (Buffett-Jerrott and Stewart 2002;Lader 1994), relapse, and resistance to treatment (Starcevic 2012). A better understanding of the processes underlying human emotions may provide support for the administration of relaxation techniques such as meditation as a treatment for stress-related and anxiety disorders, as well as other psychiatric illnesses involving mood (Manzoni et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Although benzodiazepines are highly efficacious compounds, their use is limited by significant side effects, which can include sedation, amnesia, tolerance, dependence, and withdrawal (Buffett-Jerrott and Stewart, 2002;Shader and Greenblatt, 1993;Woods, 1998). These effects are believed to be mediated by their specific interactions with the GABA A receptor.…”
Section: Voltage-gated Ion Channels: Novel Approaches To Modulation Omentioning
confidence: 99%